Improved Control Mechanism of Bottleneck Bandwidth and Round-Trip Propagation Time v3 Congestion with Enhanced Fairness and Efficiency - Hung-Chi Chu; Hao-Chu Chiang (Engineering Proceedings)
The widespread adoption and popularity of various applications have led to large and frequent data transmissions, resulting in network congestion, high packet delays, and packet loss. In 2016, Google proposed the Bottleneck Bandwidth and Round-trip propagation time (BBR) algorithm to mitigate network congestion. However, its network fairness is poor. Consequently, BBRv2 and BBRv3 were introduced in 2018 and 2023 as improved versions. Although BBRv2 exhibited enhanced fairness, its bandwidth utilization rate was lower than that of other existing methods. Meanwhile, BBRv3 still lacked bandwidth fairness in its initial transmission. Therefore, we have improved the fairness based on BBRv3 by considering the maximum sending rate and utilizing connections at different times. Good fairness and bandwidth utilization are maintained on the bottleneck bandwidth with the improved method. The method outperforms Cubic Binary Increase Congestion Control (CUBIC) and BBRv3 in terms of bandwidth utilization and network usage fairness.